HUBUNGAN USIA DENGAN IMPLEMENTASI PERILAKU HIDUP BERSIH DAN SEHAT MASA PANDEMI COVID 19 MAHASISWA KEBIDANAN STIKES AKBIDYO - Wiwin Hindriyawati; Winarsih Winarsih (Jurnal Medika Cendikia, 2022)
Health is important for every human, a healthy body can perform daily activities to the maximum. Health cannot be obtained directly but requires a behavior that is implemented with continuous maintenance and behavior. Clean and Healthy Living Behavior (PHBS) is a behavior that is carried out with awareness so that family members or family members can help themselves in the health sector and play an active role in health activities in the community. Prevention is better than cure, this health principle is the basis for implementing the PHBS program. (Ministry of Health RI, 2016). December 2019 it was reported that a new type of coronavirus or SARS-CoV-2 first appeared. The virus that causes respiratory problems has spread to almost all countries in the world. Seeing the spread of the corona virus, the world health organization WHO has declared that Covid-19 is a global pandemic. (Karo, 2020). This research is a quantitative research with cross sectional design and descriptive correlation. Respondents were 41 students using total sampling. Data collection tool a questionnaire. The results of the univariate study are 80.5% of adolescent students and 19.5% of early adulthood, and the implementation of behavior is quite high for PHBS 39.0%. The results of the bivariate test using the Kendall's Tau-b test showed a significant relationship p value: 0.003 . It is hoped that there will be good cooperation between the campus covid 19 task force and students to disseminate information about PHBS and how to implement healthy living behaviors in daily life.